Cultural Memory: to 100th Anniversary of A. M. Gorky Stay in German Saarov - T. V. Kudryavtseva (Научный диалог)
The article presents evidence of A. M. Gorky’s stay in the German city of Saarov in 1922-1923. Within the framework of the historical-contextual approach, an attempt was made to show how the mechanisms for preserving and updating memory function in relation to a particular writer. We are talking about the world-famous classic of Russian / Soviet literature — A. M. Gorky. It is traced how his personality and creative heritage, which once became part of world literature, are perceived in a foreign cultural space of the 21st century (namely, a century after Gorky’s stay in Germany at the beginning of the 20th century). The analysis involves both material objects of culture (museum complexes, monuments, etc.), onomastic geolocation, and elements of memorial culture related to written sources. These are the memoirs of contemporaries, research, as well as the actualization of Gorky’s work at the level of mass consciousness (the creation of a certain citation book from Gorky’s works, etc.). It is concluded that Gorky’s personality and work continue to be an integral part of the memorial culture of Germany, and his name, despite the change of generations, ideologies and geopolitical shifts, has not been erased from the cultural map of this country.